Nutritional composition and transcriptome analysis of the newly hatched Anguilla japonica from embryo to preleptocephali obtained from artificial reproduction - Li, Kang; Li, Yuangu; Li, Tiezhu; Cui, Rongfeng; Liu, Liping (Frontiers in Marine Science, 2024)
The starter diet for Japanese eel (Anguilla japonica) has always been a difficult problem for the realization of total artificial reproduction. Therefore, this research analyzed the nutritional composition of artificially fertilized eggs, and transcriptome of samples from early hatchlings of fry to better understand nutrients requirements. The composition of crude lipid and crude protein in fertilized eggs was 7.24% ± 0.32% and 10.56% ± 0.41%, respectively. Seven kinds of essential amino acids (EAA) were detected but took a comparable lower content (3.19%) than other marine fish eggs. We randomly assembled 265.74 million clean reads and identified 1751 differentially expressed genes (DEGs) (P < 0.01) from pre-leptocephalus larvae. A total of 23 KEGG pathways related to the digestive and metabolic system were detected. Genes related to the secretion pathway of saliva, pancreatic juice and other digestive juices were significantly changed. Transcriptome analysis showed that as larvae aged, glycolytic metabolism and the transcription level of hexokinase (HK) increased significantly (day 0 to 12). This study will facilitate future studies on the nutrition of A. japonica larvae and other biological traits to reproductive research.